(untitled) (Rudarsko-geološko-naftni zbornik, 2019)
Repeated blasting leads to progressive and cumulative effects on blast-induced damage zones in which the extension zone and the intensity of weakness are dynamic. This paper presents the results of an experimental study intended to examine cumulative weakness intensity due to repeated blasting to simulate a bench blasting situation in open pit min- ing. For this purpose, four concrete blocks were made which were subjected to two different blasting patterns. A grid was designed to measure ultrasonic wave velocity in the blocks. The blocks were blasted by a detonating cord and their weak- ness intensity index was defined by calculating the difference between wave velocity before and after blasting rounds. The results show that weakness intensity due to the second blasting round was increased when compared to the results of the first blasting round. In addition, dispersion of weakness produced by the second blasting round was more uni- form. Moreover, explosive energy distribution in terms of the initiation and propagation of fractures caused by the sec- ond blasting round affected the performance of the second blasting round energy. This study increased the current un- derstanding of the repeated blasting cumulative effect on a surrounding rock mass in terms of weakness which affects the mechanical properties of a rock mass.